'Walking a tightrope': India's challenges in meeting the 2030 Sustainable Development Agenda with specific reference to climate change. (September 2016) - Pritchard, Bill
Abstract : India is walking a tightrope in international climate change policy. As an emerging economic power, it is keen to be seen as a contributor to international climate solutions. However, the grinding poverty that dominates the lives of much of the Indian population generates a domestic political agenda in which economic development is constructed as paramount. The Government of India has justified these two positions by emphasizing its low level of historical cumulative emissions, thereby giving space to its claims for relatively modest emission reduction targets. These insights shed light more broadly on environmental governance and the SDGs. The Government of India is committed to the SDG of climate action, but committed a little more strongly to other SDGs that are affixed more centrally to material progress.